Graduate research student policy: A study of United Kingdom universities' practices - Zainal Abiddin, Norhasni (Eurojournals, 2006)
In every university, there is code of practice or policy for graduate research student which contained in the student handbook. Every student will be given this handbook during their registration at the university. Part of this policy was designed to protect the student's interest and welfare by stating the responsibility of the student, supervisor, school and effective ways of supervision. The question is how far this policy has been practiced and implemented effectively? Hence, there were 40 graduate research student policies have been studied from 40 universities in the United Kingdom. There were also 110 foreign graduate students had involved in order to obtain the information needed. It was found in the research that 74% of the respondents had agreed that the policy is very helpful and worked. This paper will identify the most effective ways in practicing this policy towards the effectiveness in graduate research student supervision.